Assessment of the E?ect of Combined Antenatal and Postnatal Counselling on Postpartum Modern Contraceptive Use - K Shwetha; B G Sowmya (Asian Journal of Medical Research, 2020)
Background: Postpartum contraception is one of the means to prevent rapid repeat pregnancies to ensure good health outcomes in both mother and baby. The present study was conducted to assess the effect of combined antenatal and postnatal counseling on postpartum modern contraceptive use. Subjects and Methods: 124 pregnant women at more than 24 weeks of gestation were divided into 2 groups. Group I (only prenatal education group). Women in Group II were given additional contraceptive education at six weeks after hospital discharge (both antenatal and postnatal education). Results: Contraceptive methods used before pregnancy were modern seen in 42% and 48%, traditional in 30% and 32% and no method in 28% and 20%in group I and II respectively. After pregnancy was modern seen in 48% and 60%, traditional in 45% and 38% and no method in 7% and 2%in group I and II respectively. The difference was non-significant (> 0.05). Conclusion: Authors found that family planning education should be provided to all pregnant women during antenatal care. There was no improvement in methods of contraception in both groups even after pregnancy.